The Urgency of Digital Oversight and Literacy in Balancing the Rights and Obligations of Debtors and Creditors in Online Loan Services - Tajuddin Noor; Suhaila Zulkifli (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2026)
The rise of the digital economy has been greatly facilitated by the development of electronic lending and transactions, particularly in terms of increasing access and corporate access to funding. Protection of users' personal information, as stipulated in Law Number 11 of 2008 concerning Electronic Information and Transactions and Regulation of the Minister of Communication and Informatics Number 20 of 2016, must always be considered in implementing these activities. Only institutions registered and providing services in accordance with Financial Services Authority Regulation Number: 77/POJK.01/2016 are permitted to offer financial technology (fintech) lending services. Using a legislative approach and normative legal techniques, this research is supported by secondary legal materials such as legal philosophy and literature. Based on the research findings, legal protection for creditors and debtors in fintech lending services has been made possible by various legal instruments. However, several obstacles remain in its implementation, particularly related to the scope of personal information and collection methods that violate ethical standards. Law Number 8 of 1999 concerning Consumer Protection provides legal protection for debtors, while Law Number 4 of 1996 concerning Mortgage Rights provides legal protection for creditors. Therefore, to achieve a fair, proportional, and sustainable balance of rights and obligations between debtors and creditors, stricter supervision, better digital literacy, and consistent law enforcement are needed.